Immunization with a Combination of Integral Chlamydial Antigens and a Defined Secreted Protein Induces Robust Immunity against Genital Chlamydial Challenge - Li, Weidang (American Society for Microbiology (ASM), 2010)
We have previously demonstrated the efficacy of recombinant chlamydial protease-like activity factor (rCPAF; a secreted chlamydial protein) in inducing antigen-specific CD4(+) T cell/gamma interferon (IFN-γ)-mediated but not antibody-mediated chlamydial clearance and reduction of upper genital tract (UGT) pathological sequelae. Since chlamydial integral antigens may induce neutralizing antibody protection, we further evaluated induction of protective immunity using a combination of rCPAF and UV-inactivated chlamydial elementary bodies (UV-EB) against vaginal chlamydial challenge in comparison to immunization with the individual components or live EB. The rCPAF-UV-EB immunization induced a significantly enhanced anti-UV-EB cellular and antibody response and a reduced anti-CPAF cellular and antibody response, compared to immunization with the respective individual components. Moreover, vaccination with UV-EB and rCPAF-UV-EB induced serum antibodies that neutralized chlamydial infectivity. The rCPAF-UV-EB immunization resulted in a significant reduction of vaginal chlamydial shedding and induced earlier bacterial clearance than vaccination of mice with the individual components. Importantly, the UGT sequelae were significantly reduced in mice immunized with rCPAF or rCPAF-UV-EB, but not in those immunized with UV-EB alone, and approached the levels of protection induced by live EB. These results collectively suggest that a combination of neutralizing antibodies induced by integral chlamydial antigens and cell-mediated responses induced by secreted proteins such as CPAF induces optimal protective immunity against genital chlamydial infections.